Actinic granuloma over photo exposed and covered parts - K, Bhavya Mani; Thiruveedhula, Haritha; Samanthula, Haritha (Journal of Pakistan Association of Dermatologists, 2023)
Actinic granuloma, also known as an annular elastolytic giant cell granuloma variant, is a chronic granulomatous condition. It is relatively a rare condition triggered by various factors like prolonged exposure to the sun, which initiate an immune response leading to changes in elastic tissue. We report a 69-year-old man who presented with a complaint of a reddish ring-like rash over both thighs, inner aspect of right elbow, back of the neck for two months. He was treated with topical tacrolimus for two months and responded well. The clinical picture of actinic granuloma is similar to that of granuloma annulare; hence they should be differentiated from each other based on histopathology. The histopathological picture of actinic granuloma mainly shows elastolysis, elastophagocytosis, and multinucleate giant cells